2019
DOI: 10.1016/s2542-5196(19)30130-5
|View full text |Cite|
|
Sign up to set email alerts
|

Attributable sources of community-acquired carriage of Escherichia coli containing β-lactam antibiotic resistance genes: a population-based modelling study

Abstract: Background Extended-spectrum β-lactamase-producing Escherichia coli (ESBL-EC), plasmid-mediated AmpCproducing E coli (pAmpC-EC), and other bacteria are resistant to important β-lactam antibiotics. ESBL-EC and pAmpC-EC are increasingly reported in animals, food, the environment, and community-acquired and health-careassociated human infections. These infections are usually preceded by asymptomatic carriage, for which attributions to animal, food, environmental, and human sources remain unquantified. Methods In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
207
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(217 citation statements)
references
References 31 publications
7
207
1
2
Order By: Relevance
“…The oral-faecal route was indicated as the most frequent route of human-to-human ESBL-EC transmission [9]. Thus, in the model, we hypothesised that hand contamination with ESBL-EC most likely occurs when: 1) a colonised person is using the toilet or 2) a person is changing the diapers of a colonised baby.…”
Section: Transmission Modelmentioning
confidence: 99%
“…The oral-faecal route was indicated as the most frequent route of human-to-human ESBL-EC transmission [9]. Thus, in the model, we hypothesised that hand contamination with ESBL-EC most likely occurs when: 1) a colonised person is using the toilet or 2) a person is changing the diapers of a colonised baby.…”
Section: Transmission Modelmentioning
confidence: 99%
“…High prevalence of ESBL/pAmpC-producing bacteria in poultry flocks (from 0.3 up to 100%) and poultry products (from 3.3 up to 94.5%) is also reported from several other European countries ( Saliu et al., 2017 ), indicating broilers to be an important source of ESBL/pAmpC-producing bacteria. Although the contribution from poultry (meat) to human carriage of ESBL-producing E. coli seems less important than initially perceived ( Mughini-Gras et al., 2019 ), all attempts to contribute to reducing emergence and spread of antibiotic resistance in humans and animals are important from a One Health perspective ( World Health Organization, 2018 ). Moreover, direct contact with poultry (e.g., people working or living on a poultry farm) could be a transmission route of ESBL/pAmpC-producing bacteria ( Dierikx et al., 2013b , Huijbers et al., 2014 , Huijbers et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study in Vietnam found that the colonization rate with mcr-E. coli was 9% in the urban population, but was 33% among farmers with exposure to poultry [ 27 ]. However, community-associated transmission as observed for ESBL- E. coli is also possible [ 28 ].…”
Section: Discussionmentioning
confidence: 99%